The Effect of Service Quality And Relationship Marketing Towards Customer Loyalty for Sharia Banking (Sharia Banking Study in Makassar Indonesia) - Basalamah, Muhammad Ridwan; Moeljadi, Moeljadi; Sunaryo, Sunaryo; Sudjatno, Sudjatno (International Review of Management and Marketing, 2018)
This research aims to empirically test and explain the effect of service quality and relationship marketing towards customer loyalty through the fairness (profit share) and customer satisfaction at Sharia General Bank in Makassar, Indonesia. Data analysis method which use is SEM (Structural Equation Model) with the use of AMOS programme. This approach analysis is quantitative. Service quality affected significantly upon fairness in profit share system and customer satisfaction while relationship marketing affected in customer satisfaction only. This research only take sharia bank customer as the sample and confine the experiment subject in Makassar only. The increase in customer service for those aspectis hoped to build the customer strength to the sharia bank market share. The application of allegiance in sharia banking system would append customer satisfaction value among services offered by the bank and increase the loyalty and product sales of the bank entirely. Keywords: Service Quality, Relationship Marketing, Customer Loyalty, Customer Satisfaction, Fairness JEL Classifications: M3